Activities Of Fermented Maman (Cleome Gynandra L) On Blood Sugar Level In Hyperglycemic White Rats - Restusari, Lily; Muharni, Muharni; Fitri, Fitri; Sjahjadi, Novilla Rezka (Journal of Local Therapy, 2023)
Abstract:. Cleome Gynandra L. (called as “Maman” in Riau) is a traditional medicine used for diabetes, anti-aging, anti-cancer and cardiovascular diseases prevention. This research aimed to find out the activities of Fermented Maman on blood glucose concentrations of hyperglycemic male white rats. The study was an experimental research, using the Post Test Only Control Group Design, that carried out 5 months at Riau Ministry of Health Poltekkes Laboratory. Data were analayzed by ANOVA Multivariate than continued with Duncan multiple range test. The results of this study indicate that Fermented Maman can reduce blood sugar levels but, the metformin group had a higher reduction compared to the control group negative, positive and Fermented Maman. Metformin reduces blood sugar levels better than Fermented Maman. It is necessary to add the time of Fermented Maman and research used metformin with simultaneous fermentation in groups of male white rats with dosage variations.